Practitioner Perceptions of Emotions Associated with Pain: A Survey - Walker, Scott (Elsevier, 2005)
OBJECTIVE: To discover whether chiropractors consider that emotional factors are associated with pain presentations in their patients and if so, what methods they use to investigate these factors and what strategies they use to manage them. DESIGN: A telephone survey of chiropractors in Australasia (Australia and New Zealand) and North America (America and Canada). A database of practitioners was obtained for each region. A phoning protocol was established in each region to standardize the survey approach. SETTING: Private practice of chiropractic. METHOD: Chiropractic centers were telephoned and the attending chiropractor(s) were asked to complete a phone survey. The survey consisted of a series of short questions designed to establish the main techniques used in the practice. Questions focused on whether emotional factors of the patient were recognized and addressed and what role emotional factors play in the management of the patient. SAMPLE: Subjects were registered/licensed chiropractors listed in a publication of the largest association of practitioners in their region. RESULTS: In Australasia and North America just under half of practitioners surveyed (45.8% and 50.5% respectively) used a technique to evaluate any impacting emotions on the presenting condition. Additionally, 36.3% of Australasia and 33.3% of North America practitioners had a technique to treat emotional factors in the patient. The study also suggests that over 90% of Australasian chiropractors and 80% of North America chiropractors consider emotional factors important in pain presentations. CONCLUSION: This study found that a substantial number (80–90%) of the chiropractors surveyed believe that emotional factors influence pain syndromes. However, less than half of these practitioners report that they are able to evaluate emotional factors and approximately only a third report that they are able to treat them. This study shows there is a need for further research of chiropractors to be able to evaluate emotional factors and techniques that can be used to rectify emotional components of their patients' pain syndromes.